Diagnostic and prognostic value of inflammatory markers for patients with severe pneumonia: a meta-analysis - Meng Han (782687) (2025)
This meta-analysis evaluates the diagnostic and prognostic performance of severe pneumonia through a comprehensive meta-analysis. A systematic literature search was conducted across PubMed, Embase, Cochrane Library, Web of Science, and Scopus. Studies were included if they focused on severe pneumonia patients, assessed relevant inflammatory markers, and provided sufficient data for meta-analysis. The diagnostic meta-analysis found a sensitivity of 0.72 (95% CI: 0.64–0.79) and a specificity of 0.75 (95% CI: 0.70–0.80). Area under the summary receiver operating characteristic curve was 0.80 (95% CI: 0.76–0.83). However, these pooled estimates showed high heterogeneity (I2 > 80%), indicating substantial variation across studies and requiring cautious interpretation. Subgroup analyses revealed that procalcitonin (PCT) had the highest specificity. For predicting short-term mortality, a preliminary analysis of five studies (n = 463) showed a pooled sensitivity of 0.72 (95% CI: 0.64–0.79) and a specificity of 0.65 (95% CI: 0.59–0.70), suggesting a potential prognostic signal that needs validation in larger, prospective cohorts. Inflammatory markers are valuable auxiliary tools to support clinical judgment in assessing severity and predicting outcomes in patients with severe pneumonia. They offer moderate accuracy in distinguishing severe from non-severe cases and in predicting short-term mortality.